Tax incentives for private investment in developing countries - Anthoine, Robert; International Bar Association (Deventer ; Boston : Kluwer, 1979)
The book provides a comparative analysis of the tax laws of developed countries bearing upon direct private investment in developing countries,and a representative sample of developing country laws bearing upon the receipt of such investment
At head of title: International Bar Association, Tax Committee, Section on Business Law.
obn 24/01/2019
Loans
Keywords: Taxation; Investments, Foreign; Tax incentives